PENGENDALIAN PENYAKIT ANTRAKNOSA (Colletotrichum capsici) PADA CABAI MERAH DENGAN BEBERAPA BAKTERI SEBAGAI AGEN BIOKONTROL - Nurmayulis .; Moch. Ana Syabana; Yessica Syafendra (Jurnal Agroekoteknologi, 2013)
Research has been conducted to determine some of the bacteria of antraknosa disease control in chilies (Capsicum annum L.) with in vitro and in vivo methods conducted in the Agroecology Laboratory, Agriculture Faculty of Sultan Ageng Tirtayasa University on June to October 2011. The research uses Completely Randomized Design same factors as rizo-bacterium bio-control agents. In in vitro test for each factor composed of three level they are application of bio-control from the Pseudomonas fluorescens rizo-bacterium, application of bio-control from the Bacillus sp. rizo- bacterium, and without using a biocontrol agents. In in vivo tests of each factor is composed of 5 levels they are (CO+) without bio-control agents on uninfected chilies, (CO-) without biocontrol agents on infected chilies, with bio-control agents from the Bacillus sp. rizo-bacterium on infected chilies, with bio-control agents from the Bacillus sp. rizo-bacterium on infected chilies, and use bio-control agents combinations of P.fluorescens and Bacillus sp. rizo-bacterium repeated 5 times. Bio-control agent that comes from rhizosfer lands of chilies cultivation, are derived from Ciakar village Cikeusal sub-district, Serang, Banten. The results showed that the biocontrol agents fate with in vitro and in vivo method suppressed antraknosa disease caused by the pathogen Colletotrichum capsici and reduce chilies weight. Bio-control application with P.fluorescens rizo-bacterium group is the best treatment in in vitro test. While in in vivo test, biocontrol agents application of P.fluorescens rizo- bacterium is the best treatment in decrease the incubation period, incidence of disease, and disease antraknosa intensity in chilies, while in decrease in weight shrinkage chilies The best treatment is shown in biocontrol agents of the Bacillus sp. rizo-bacterium.